Wyklejanie, dyspozycje i performatyka w koncertach fortepianowych Bogusława Schaeffera - Atys, Szymon (Res Facta Nova, 2022)
Bogusław Schaeffer (1929–2019) was one of the most prominent figures of the Polish musical avant-garde in the 20th century. This article focuses on Schaeffer’s six Piano Concertos and is based on a logocentric analysis of the pieces. Studying Schaeffer’s declared aesthetics has revealed that ‘innovation’ (invention of something without precedence) was a key concept organising his music, which became the foundation of the performed analysis. Subsequently, the pieces are described by areas of musical material and other aspects of composition (technology of sound, notation, melosphere, chronosphere, sonosphere, texture, form and performance). Three newly discovered aspects of Schaeffer’s compositional craft are distinguished: collage of the composer’s own musical material, practical consequences of the composer’s declared ‘orchestral dispositions’ technique and theatrical aspects of musical performance. Their aim is interpreted as devaluing the role of the musical material in favour of musical texture and the executional act. Contradictions noticed in Schaeffer’s compositional craft lead to the conclusion that Schaeffer’s late music can be described as an example of Said’s ‘Late style’.